2011
DOI: 10.5366/jope.2011.05
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Four clonal oil palm materials namely AVROS, Yangambi, La Me and NIFOR and two DxP hybrid Yangambi, grown on terraced and unterraced fields were subjected to irrigated and non-irrigated conditions. There were significant differences in all leaf nutrient concentrations for all the planting materials for both terrain and irrigation conditions. For nonirrigated palms, most of the leaf nutrients were higher than the irrigated palms, especially K and Mg concentrations. Most of the leaf nutrient concentrations in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Also described in the literature are the marginal values of nutrients. Woittiez et al [12] and Lee et al [15] found that Mg content is negligible, with the mean concentrations of 0.20 and 0.21 respectively. According to Jacquemard et al [16], N concentration is negligible (mean: 2.98).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also described in the literature are the marginal values of nutrients. Woittiez et al [12] and Lee et al [15] found that Mg content is negligible, with the mean concentrations of 0.20 and 0.21 respectively. According to Jacquemard et al [16], N concentration is negligible (mean: 2.98).…”
Section: Resultsmentioning
confidence: 97%
“…Yadegari et al [3] determined the optimal P, K and Mg levels to be 0.17, 1.05 and 0.30 respectively. According to Lee et al [15], N, P and K concentrations are optimal, with respective values of 2.71, 0.17 and 1.03. Ibrahim et al [17] determined that N, P and Mg concentrations were optimal with values of 2.79, 0.15 and 0.32 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the leaf nutrient content especially Mg tends to be higher in circle zone fertilization due to the absence of competing weeds in the circle weeding. This is because weeds absorb nutrients through the competition when fertilization is carried out on oil palm plantations [25].…”
Section: Leaf Nutrients Contentmentioning
confidence: 99%